Iridium oxide microelectrode arrays for in vitro stimulation of individual rat neurons from dissociated cultures - Eick, Stefan; Wallys, Jens; Hofmann, Boris; Van Ooyen, André; Schnakenberg, Uwe; Ingebrandt, Sven; Offenhäusser, Andreas (Frontiers in Neuroengineering, 2009)
We present the first in-vitro extracellular stimulation of individual neurons from dissociated cultures with iridium oxide (IrOx) electrodes. Microelectrode arrays with sputtered IrOx films (SIROF) were developed for electrophysiological investigations with electrogenic cells. The microelectrodes were characterized with scanning electron and atomic force microscopy, revealing rough and porous electrodes with enlarged surface areas. As shown by cyclic voltammetry and electrochemical impedance spectroscopy, the large surface area in combination with the good electrochemical properties of SIROF resulted in high charge storage capacity and low electrode impedance. Thus, we could transfer the good properties of IrOx as material for in-vivo stimulation electrodes to MEAs with electrode diameters as small as 10 µm for in-vitro applications. Single rat cortical neurons from dissociated cultures were successfully stimulated to fire action potentials using single or trains of biphasic rectangular voltage-controlled stimulation pulses. The stimulated cell’s membrane potential was simultaneously monitored using whole-cell current-clamp recordings. This experimental configuration allowed direct evaluation of the influence of pulse phase sequence, amplitude, and number on the stimulation success ratio and action potential latency. Negative phase first pulses were more effective for extracellular stimulation and caused reduced latency in comparison to positive phase first pulses. Increasing the pulse amplitude also improved stimulation reliability. However, in order to prevent cell or electrode damage, the pulse amplitude is limited to voltages below the threshold for irreversible electrochemical reactions at the electrode. As an alternative to increasing the amplitude, a higher number of stimulation pulses was also shown to increase stimulation success.